Consommation des anti-inflammatoires non stéroïdiens lors de la préparation au Grand Raid 2016 à La Réunion - Lai-Cheung-Kit, I.; Lemarchand, B.; Bouscaren, N.; Gaüzère, B.-A. (Science & Sports, 2019)
Introduction: The Ultra-trail® has enjoyed unlimited popularity over the past decade. During this type of race, ultra-marathon runners regularly force their bodies to exceed their physical and mental limits, which is why they sometimes use non-steroidal anti-inflammatory drugs (NSAIDs). Objective: The aim of this study was to determine, for the first time, the prevalence, type of use and level of awareness of NSAIDs among the ultra-marathon runners training for the Grand Raid 2016 edition in Reunion Island. (167km; 9700m ascending elevation gain). Methods: Self-reporting, prevalence, descriptive epidemiological survey. A self-reported questionnaire concerning the use of NSAIDs and awareness of potential risks and adverse effects was sent anonymously by email to each of the ultra-marathon runners registered for one of the Ultra-trails® at the Grand Raid 2016. Results: A total of 30.7% (n=1142) of the 3725 registrants responded to the questionnaire. Four hundred and nine (35.8%) ultra-marathon runners reported using NSAIDs in the year prior to the race (January 1, 2015 to October 20, 2016). Among NSAID users, 31.5% (n=129) used NSAIDs without a prescription. The main reason stated was the treatment of acute pain. The majority would rarely use NSAIDs and 73% (n=300) would usually use them for a short period of time (<3consecutive days). Apart from the anti-inflammatory and analgesic effect, most ultra-marathon runners were unaware of the properties of NSAIDs and the risks of complications other than digestive and/or renal. Conclusion: The prevalence rate of NSAID use is high among ultra-marathon runners, who have only limited knowledge of their properties and side effects. Self-medication is important. Education of ultra-trailers on the benefits and risks of NSAIDs should be strengthened, involving their general practionner.